Development of type 1 diabetes mellitus blood glucose level simulation mobile application - Mohamad Akbar, Asyraf Aiman (2020)
Most diabetes mobile applications in the market right now only focused on receiving input of a diabetes patients’ previous food consumption, insulin intake and their corresponding measured blood glucose to help them manage the condition by displaying the information back in a more organized form. This research proposes a new application that instead process the input from the user and generate a simulation of the patient’s predicted future blood glucose level trend. The application has been developed in this study which is then compared and validated with other works. The mathematical model used has already been validated by Lehmann & Deutsch (1992), and hence in the study, the application was tested if it can replicate the simulation of clinical data used by them. The application’s simulation is slightly off due to lack of initial condition data but for the most part was close to the original simulation. The features and purpose of each section in the application was discussed with a demonstration on how the application works. This study found that although application can be used to show the trend of blood glucose from meal consumption and administration of insulin, it is not reliable enough to be able to predict with 100% accuracy of future blood glucose level with just the information from user input data. The application however, has potential as an educational tool where diabetes patient can learn about the effect of carbohydrate, insulin, and the change of these input to their blood glucose level. This was shown by a simulation of different insulin injection time using the application to show the effect it has on blood glucose level which demonstrate some of the things that T1DM patients can learn from the application. One of the limitations of the application is it does not incorporate physical activity into the simulation. Hence, it is recommended that future application to take physical activity into consideration. Further studies on glucose-insulin dynamics with physical activity is also recommended as only a few existing models for this are currently found.